(untitled) (MAUSAM, 1966)
Geomagnetic disturbance daily variation SD(H) and storm-time hourly depressions in H occurring at the magnetic observatories, Trivandrum and Annamalainagar, stations close to the magnetic equator are compared with those occurring at Alibag (mag. lat. 13oN) to show that the disturbances are of about the same magnitude during the night-time at the three observatories, while during the day-time disturbance magnitudes near the magnetic equator are enhanced in varying degrees depending on the type of disturbance. It is inferred that geomagnetic disturbances arise at least partly from E-layer electric currents and that such currents are augmented at the magnetic equator during the day. The fact that the disturbances are not enhanced at the reagnetic equator during the night must be due to the insignificant ionization in the E-layer and the absence of inhibition of vertical Ran currents at night.